O papel do médico no apoio à crise dos refugiados - baseado numa experiência de voluntariado no campo de refugiados de Mavrovouni na ilha de Lesvos, Grécia. - Cunha, Ana Francisca Loureiro Santos da (2025)
Humanitarian medicine is a field of medicine focused in providing health care to people who find themselves in particularly precarious conditions, namely in emergency situations, natural disasters, humanitarian crises and conflict zones. Although all medicine, in its essence, is humanitarian, this field of medicine, in addition to its therapeutic objective, seeks to alleviate human suffering and promote human rights, particularly the right to health. The challenges and needs of humanitarian medicine are growing and make the role of the humanitarian doctor more difficult and challenging.The refugee crisis, particularly in the Mediterranean, is one of several examples of humanitarian crises where humanitarian medicine and doctors play a fundamental and extremely important role.A case report was carried out with the aim of identifying the role of the humanitarian doctor, as well as the main challenges and needs inherent to the practice of humanitarian medicine, and to alert people to its growing importance in today's society. This was based on a voluntary internship carried out in the Mavrovouni refugee camp on the island of Lesvos, Greece, through Boat Refugee Foundation, an NGO that provides medical and psychological support within the camp. A description is given of the preparatory moments, daily life, the challenges identified and testimonies were collected from different agents. The data collected was then analysed critically and reflexively.The Mavrovouni camp is home to thousands of refugees and migrants of various nationalities who face difficult living conditions and significant challenges related to overcrowding, lack of security, poor hygiene, insufficient medical and food resources, among others.The data collected and described, based on the entire experience in the Mavrovouni refugee camp, has been critically analysed and a general reflection is made on the experience in the camp, needs, challenges, factors to be improved and what can be done in this regard. The role of the doctor in supporting the refugee crisis is discussed and the challenges and limitations faced by the doctor and humanitarian medicine are recognised. It´s, also, highlighted the growing importance of humanitarian medicine in today's society and the actions needed to attract more people and professionals to this type of activity.